(untitled) (Proceedings of International Educators Conference, 2023)
In our article, the difficulties in teaching vocabulary to young language learners are analyzed in examples. In the emergence of science until now, the history of mankind and its relation to language learning as a scientific issue, various theories and theories and scientific debates from the present day and the Renaissance period, various scientific views on the difficulties in teaching vocabulary to young language learners we can study the existence of various scientific debates in the literature and iterate data.